P‐182L: Late‐News Poster: A True Circular Flexible AMOLED Display for Wearable Applications. Issue 1 (June 2015) - Jen, Ko‐Ruey; Lin, Li‐Fong; Chen, Yi‐Chien; Wang, Pei‐Yun; Huang, Yu‐Chun; Lin, Kuan‐Heng; Yang, Chieh‐Hung; Huang, Feng‐Yu; Wang, Cheng‐Liang; Lin, Jia‐Hua; Lee, Wen‐Hui; Yu, Chih‐Yu; et al.
Abstract : A 1.25" circular plastic‐based AMOLED display has been developed for wearable application. By locating gate drivers in the active area and bending the plastic substrate outside the active area of the panel, we successfully realized a display with true circular shape and slim border, respectively.